2017
DOI: 10.1021/acs.jmedchem.6b01907
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (R)-1-(3-(4-Amino-3-(3-chloro-4-(pyridin-2-ylmethoxy)phenyl)-1H-pyrazolo[3,4-d]pyrimidin-1-yl)piperidin-1-yl)prop-2-en-1-one (CHMFL-EGFR-202) as a Novel Irreversible EGFR Mutant Kinase Inhibitor with a Distinct Binding Mode

Abstract: On the basis of Ibrutinib's core pharmacophore, which was moderately active to EGFR T790M mutant, we discovered novel epidermal growth factor receptor (EGFR) inhibitor compound 19 (CHMFL-EGFR-202), which potently inhibited EGFR primary mutants (L858R, del19) and drug-resistant mutant L858R/T790M. Compound 19 displayed a good selectivity profile among 468 kinases/mutants tested in the KINOMEscan assay (S score (1) = 0.02). In particular, it did not exhibit apparent activities against INSR and IGF1R kinases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…A series of 1 H -indazole derivatives were synthesized using structure-guided drug design from lead compound 108 by Liu et al [ 64 ] and evaluated for their epidermal growth factor receptor (EGFR) kinase activity. The results indicated that compound 109 displayed strong potencies against EGFR T790M and EGFR kinases with IC 50 values of 5.3 and 8.3 nM, respectively ( Figure 20 ).…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…A series of 1 H -indazole derivatives were synthesized using structure-guided drug design from lead compound 108 by Liu et al [ 64 ] and evaluated for their epidermal growth factor receptor (EGFR) kinase activity. The results indicated that compound 109 displayed strong potencies against EGFR T790M and EGFR kinases with IC 50 values of 5.3 and 8.3 nM, respectively ( Figure 20 ).…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…In conclusion, the action of 14 on cell growth inhibition of NCI-H1975 cells is mediated by the inhibition of EGFR phosphorylation and the subsequent inactivation of two downstream signal pathways, namely, PI3K-AKT and RAF-MEK-ERK. 10,[27][28][29][30][31][32][33][34][35][36] In order to understand the biochemical reactivity profile of allenamide as a covalent warhead, we measured the pseudofirst-order reaction 9 rate constant of GSH addition to 14 or acrylamide containing marketed drugs 1-3 (Table 4). The rate constant, k pseudo 1st , observed for GSH addition to 14 is 302.5 × 10 −3 min −1 under our experimental conditions, which is about 7 to 28-fold higher than that of 1-3.…”
Section: Resultsmentioning
confidence: 99%
“…26 In view of the robust reactivity of allenamides towards thiol groups, we hypothesized that allenamide could be used as a bioisostere of the acrylamide moiety in small molecule drug design. In order to test this hypothesis, we replaced the acrylamide moiety of 2 with an allenamide group in an irreversible EGFR kinase inhibitor model system, 10,[27][28][29][30][31][32][33][34][35][36][37][38][39] which led to a series of novel TCIs.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacophore models have also been used for identifying active molecules to mitigate the effects of mutations in many diseases [119][120][121][122] . For the cases where a sufficient number of active molecules are previously known for generating high-quality pharmacophore models, pharmacophore proves to be a powerful tool for drug 'lead' identification 116 .…”
Section: Structure-based Pharmacophore Designmentioning
confidence: 99%